2005
DOI: 10.1002/pmic.200401085
|View full text |Cite
|
Sign up to set email alerts
|

A proteome analysis of the yeast response to the herbicide 2,4-dichlorophenoxyacetic acid

Abstract: The intensive use of herbicides may give rise to a number of toxicological problems in non-target organisms and has led to the emergence of resistant weeds. To gain insights into the mechanisms of adaptation to the herbicide 2,4-dichlorophenoxyacetic acid (2,4-D), we have identified variations in protein expression level in the eukaryotic experimental model Saccharomyces cerevisiae exposed to herbicide aggression, based on two-dimensional gel electrophoresis. We show results suggesting that during the adaptati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 47 publications
5
39
0
Order By: Relevance
“…There are many works on proteome of S. cerevisiae 12 and alterations in protein abundance levels can provide clues about the mechanism of action of various drugs. 13 However, it is still difficult to estimate the target molecule of a drug from proteome information alone. In this study, we found relationship between protein synthesis inhibition and decrease of abundances of ribosomal proteins in S. cerevisiae.…”
Section: Introductionmentioning
confidence: 99%
“…There are many works on proteome of S. cerevisiae 12 and alterations in protein abundance levels can provide clues about the mechanism of action of various drugs. 13 However, it is still difficult to estimate the target molecule of a drug from proteome information alone. In this study, we found relationship between protein synthesis inhibition and decrease of abundances of ribosomal proteins in S. cerevisiae.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include case-studies based on our own experience in using Expression Proteomics to get mechanistic insights into the response and resistance to chemical stress resistance in two microbial model systems: the yeast Saccharomyces cerevisiae [19,20] and bacteria of Pseudomonas species [21,22]. One of these case-studies is then used as the basis for the laboratory and computational classes.…”
Section: Lecturesmentioning
confidence: 99%
“…This curricular unit is a mandatory discipline for around 60 students per year, as part of the Biological Engineering (40) or Biotechnology (20) curricula. These students, together with others that annually choose the discipline as an option, attend the theoretical classes and are divided in groups of 15 for computational and, when available, of 12 for wet laboratory classes.…”
Section: Teaching Expression Proteomicsmentioning
confidence: 99%
“…The global yeast response to 2,4-D, revealed by microarray and proteomic analyses, indicates the upregulation of a large number of genes involved in alternative carbon and nitrogen source metabolism (Teixeira et al, 2006a) and in the uptake and biosynthesis of amino acids (Teixeira et al, 2006a;Teixeira et al, 2005), correlating with a dramatic reduction of the intracellular concentration of amino acids (Teixeira et al, 2005). These adaptive mechanisms might be a response to the deleterious effects exerted by 2,4-D on plasma membrane lipid organization and permeability, leading to nutrient import inhibition (Bradberry et al, 2000) (Figure 2).…”
Section: Yeastmentioning
confidence: 99%